DIPLOMASI KEBUDAYAAN INDONESIA TERHADAP AMERIKA SERIKAT MELALUI KULINER (GASTRODIPLOMACY) TAHUN 2010-2016 - Sarah Patrecia Sinulingga; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Cultural diplomacy is a category of Soft Diplomacy in the implementation of a country's foreign policy. Cultural diplomacy is a manifestation of the implementation of public diplomacy. One of the cultural diplomacy instruments used by Indonesia to the United States is culinary. Diplomacy through culinary is known as gastrodiplomasi. Indonesian's Gastrodiplomacy aims to win the hearts and minds of foreigners thereby increasing interaction and cooperation with other countries.Using the theory of diplomacy is the concept of soft power by Joseph Nye, Jr and perspective of Neorealism by Kenneth Waltz, this research obtained data through literature studies and direct research to the Indonesia Ministry of Foreign Affairs.The research shows that Indonesian's Gastrodiplomacy have been done through annual festivals serving Indonesian culinary such as Indonesia Culinary Festival, participation of Indonesian government in annual culinary festival held by the United States of America and increasing the number of Indonesian restaurants in the United States of America. Culinary diplomacy also have been done through the media online, such as Youtube. It was also found that the implementation of culinary diplomacy impacts the level of Indonesian food and beverage exports to the United States and attracted the interest of the United States to visit Indonesia.Keywords: Culture Diplomacy, Public Diplomacy, Gastrodiplomacy